Halimium halimifolium: From the Chemical and Functional Characterization to a Nutraceutical Ingredient Design - Kerbab, Khawla; Sansone, Francesca; Zaiter, Lahcene; Esposito, Tiziana; Celano, Rita; Franceschelli, Silvia; Pecoraro, Michela; Benayache, Fadila; Rastrelli, Luca; Picerno, Patrizia; Aquino, Rita P.; Mencherini, Teresa (Planta Medica, 2019)
Halimium halimifolium (Hh) is a shrub used in Algerian folk medicine to treat gastrointestinal pain. An UHPLC-PDA-ESI/MSn method was developed to identify the metabolic profile of the traditionally used infusion (Hh-A) from the aerial parts. The structures of flavanols were confirmed by NMR analysis after the isolation procedure from a hydrohalcolic extract (Hh-B) that also allowed for the identification of phenolic acids, an aryl butanol glucoside, and different derivatives of quercetin, myricetin, and kaempferol. Tiliroside isomers were the chemical markers of Hh-A and Hh-B (54.33 and 36.00 mg/g, respectively). Hh-A showed a significant scavenging activity both against the radicals 1,1-diphenyl-2-picrylhydrazyl and 2,2′-Azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (EC50 = 10.49 µg/mL and TEAC value = 1.98 mM Trolox/mg infusion) and the lipopolysaccharide-induced reactive oxygen species release in A375 and HeLa cells. Moreover, the antihyperglycemic properties, by inhibiting the α-amylase and α-glucosidase enzymes (IC50 = 0.82 mg/mL and 25.01 µg/mL, respectively), were demonstrated. To upgrade the therapeutic effect, a microencapsulation process is proposed as a strategy to optimize stability, handling, and delivery of bioactive components, avoiding the degradation and loss of the biological efficacy after oral intake. Hh-loaded microparticles were designed using cellulose acetate phthalate as the enteric coating material and spray drying as a production process. The results showed a satisfactory process yield (67.9%), encapsulation efficiency (96.7%), and micrometric characteristics of microparticles (laser-scattering, fluorescent, and scanning electron microscopy). In vitro dissolution studies (USPII-pH change method) showed that Hh-loaded microparticles are able to prevent the release and degradation of the bioactive components in the gastric tract, releasing them into the intestinal environment.
Keywords: Halimium halimifolium; Cistaceae; antioxidant activity; antihyperglycemic activity; spray drying; gastro-resistant microparticles; nutraceuticals